2004
DOI: 10.1128/mcb.24.24.10844-10856.2004
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-Terminal Protein Kinase 1 (JNK1), but Not JNK2, Is Essential for Tumor Necrosis Factor Alpha-Induced c-Jun Kinase Activation and Apoptosis

Abstract: Two ubiquitously expressed isoforms of c-Jun N-terminal protein kinase (JNK), JNK1 and JNK2, have shared functions and different functions. However, the molecular mechanism is unknown. Here we report that JNK1, but not JNK2, is essential for tumor necrosis factor alpha (TNF-α)-induced c-Jun kinase activation, c-Jun expression, and apoptosis. Using mouse fibroblasts deficient in either Jnk1 or Jnk2, we found that JNK1 was activated by TNF-α, whereas JNK2 activation was negligible. In addition, JNK2 interfered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
199
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(221 citation statements)
references
References 34 publications
20
199
2
Order By: Relevance
“…Overexpression of JNK1b1 increases resistance to vesicular stomatitis virus-induced cell death in 3T3 fibroblasts, whereas overexpression of JNK1a1 and JNK1b1 potentiates cisplatin-and doxorubicin-induced cell death in sarcoma cell lines (Han et al, 2002;Koyama et al, 2006). Previous studies have demonstrated a role for either JNK1 or JNK2 in TNFa-induced apoptosis (Dietrich et al, 2004;Liu et al, 2004). Our results show that the chief JNK isotype activated by DR4 and DR5 is JNK1.…”
Section: Jnk1a1 Has An Antiapoptotic Functionsupporting
confidence: 49%
“…Overexpression of JNK1b1 increases resistance to vesicular stomatitis virus-induced cell death in 3T3 fibroblasts, whereas overexpression of JNK1a1 and JNK1b1 potentiates cisplatin-and doxorubicin-induced cell death in sarcoma cell lines (Han et al, 2002;Koyama et al, 2006). Previous studies have demonstrated a role for either JNK1 or JNK2 in TNFa-induced apoptosis (Dietrich et al, 2004;Liu et al, 2004). Our results show that the chief JNK isotype activated by DR4 and DR5 is JNK1.…”
Section: Jnk1a1 Has An Antiapoptotic Functionsupporting
confidence: 49%
“…3a). These are the JNK1a1 and JNK2a1 isoforms of JNK (Liu et al 2004). The increased amounts of activated JNK1/2 may reflect the increased levels of JNK1/2 in the treated cells, or may indicate that JNK1/2 are activated to a low level in SB203580 treated cells.…”
Section: Characterisation Of Stress Kinase Effector Pathwaysmentioning
confidence: 99%
“…Some of these differences were attributed to differential phosphorylation of the E3 ubiquitin ligase Itch by JNK1 and JNK2 isoforms (22). The preferential activation of Itch by JNK1 (23) may also explain the selective involvement of JNK1 rather than JNK2 in TNF-␣-induced cell death (24). Isolated JNK1 but not JNK2 deficiency results in reduced adiposity and increased insulin sensitivity in mouse models of obesity (10).…”
mentioning
confidence: 99%